ALARM DRIVER BOARD FOR MICROELECTRONIC PACKAGE LEGACY HANDLERS - Cruz, Lorenz Jules P; Jaca, Michael Joe D; Ortiz, Glenn N; Enojas, Mark Joseph B (Journal of Agriculture and Technology Management; Vol 24 No 3 (2021): Vol 24 No 3 (2021): Vol 24 No 3 (2021): Journal of Agriculture and Technology Management (JATM) Volume 24 ICAMEROB Edition, 2021)
This study was conducted to enhance the overall equipment efficiency by designing and developing an alarm driver board for tower lights and annunciators of the legacy handlers in microelectronic packaging. Audible and visible alarms are primarily used for monitoring the status of the legacy handler machines at a distance. These are important to manufacturing personnel, that when these devices fail, production can be compromised and translates into downtime. In this study, an alarm driver for tower light and annunciators have been developed to satisfy conditions for monitoring and control of status of the legacy handlers. A proto-shield printed circuit board was designed to handle input and output signals. It was made up of Optocouplers and Darlington transistors which also serves as a protection for both the handler and the microcontroller. An Arduino microcontroller unit was used to handle controls to satisfy the alarm conditions. An additional protection circuit was developed to avoid possible errors on the control system. Many trials were conducted supposing jams in the handlers. In result, the alarm driver board developed showed outstanding reliability. This setup is recommended for implementation to other handlers in the manufacturing of microelectronic packages.